Guarding the Guardians civilian control of nuclear weapons in the United States - Feaver, Peter 1961- (Cornell Univ. Press, 1992)
Few problems of national security have remained as critical in the post-Cold War era as those raised by the command and control of nuclear weapons. Should nuclear arsenals be overseen by civilians rather than military experts? How can effective civilian control be ensured? In this lucid and penetrating book, Peter Douglas Feaver tells the story of U.S. nuclear custody policy from 1945 to the present and offers a new framework for approaching the issue of nuclear command and control. Feaver first examines the fundamental constraints and dilemmas inherent in the operation of nuclear command and control. He provides an overview of civilian control of each component of nuclear operation, with reference to three major factors: the president, who has the legal authority to order the use of nuclear weapons; key military officers who are authorized to detonate weapons without the president's permission; and lower-level officers who have physical control of the weapons. Feaver next offers a model identifying factors that explain changes in civilian control policy over time. Drawing on extensive interviews and recently declassified government documents, he then provides a rich historical account of nuclear weapons custody, paying particular attention to the Truman, Eisenhower, and Kennedy administrations. Guarding the Guardians will be an essential resource for political scientists, policy-makers, security affairs specialists, historians, and anyone concerned with addressing the hazards created by nuclear arms.
Keywords: Armas atómicas - EE.UU; Kernwapens; Parlementaire controle; Supremacía civil sobre la militar - EE.UU; Nuclear weapons -- United States; Civil supremacy over the military -- United States; Kernwaffe; Regierung; Rüstungsbegrenzung; Politische Kontrolle; Kontrolle; USA; United States -- Military policy